Unveiling viral diversity and dynamics in mosquitoes through metagenomic analysis in Guizhou Province, China - Yan Linghu; Rui-Si Hu; Xiao-Min Tang; Rong-Ting Li; Wei-Yi Li; Jia-Hong Wu (Infectious Diseases of Poverty)
Abstract Background Poverty, disease, and vector ecology intersect to present ongoing health threats, particularly in ecologically sensitive regions. Guizhou Province in China, with its complex karst topography and rich biodiversity, offers a unique environment to study mosquito-borne viral transmission. Despite over 5000 reported cases of Japanese encephalitis in the past two decades and the detection of Zika virus in 2016, the virological landscape of this region remains poorly understood. This study aims to characterize the mosquito-associated virome, assess viral diversity, and identify factors influencing transmission dynamics in Guizhou Province. Methods Between 2021 and 2022, we conducted a 2-year mosquito surveillance across eight ecologically distinct regions in Guizhou Province. Adult mosquitoes were collected using a variety of methods, including BG Mosquitaire CO2 traps, mosquito-killing lamps, manual collection, human bait traps, and oviposition traps. To investigate the virome diversity and dynamics within mosquito populations, we performed metagenomic sequencing and bioinformatics analysis on pooled mosquito samples collected from geographically diverse sampling sites. Results We collected more than 40,000 adult mosquitoes, primarily belonging to four genera: Aedes, Anopheles, Armigeres, and Culex. Dominant species included Aedes albopictus, Anopheles sinensis, Armigeres subalbatus, and Culex tritaeniorhynchus. Notably, we report the first provincial record of the Anopheles baileyi complex, expanding the known distribution of mosquito vector in this region. Viral metagenomic sequencing, coupled with bioinformatic analysis, identified 162 viral contigs, including 140 known and 22 previously uncharacterized viruses. We experimentally confirmed the genotypes of three medically important zoonotic viruses: Japanese encephalitis virus (JEV-GI), Getah virus (GETV-GIII) and Banna virus (BAV-A2). Comparative analysis of viral abundance across mosquito species revealed that Aedes albopictus populations in Guizhou harbor a distinct virome composition, diverging from those reported in other geographic regions. Conclusions This study presents the comprehensive characterization of the mosquito-associated virome in Guizhou Province, providing critical insights into viral diversity, vector competence, and transmission dynamics within karst ecosystems. The detection of multiple zoonotic viruses highlights the need for strengthened surveillance and targeted public health interventions in this region.